Strategy change and adaptation in a Family business: the case of the Laboratory Clinisul - Sausen, Jorge Oneide; Forgiarini, Lizandra; Machado Pozza Fucks, Tais (REBRAE, 2015)
The main purpose of this study is to establish a dialogue between strategic fit and experience in Clinisul Laboratory, clinical analysis, located in San Ângelo/RS, identifying and analyzing the strategies involved in organizational change, in light of actions taken by the managing partners order to identify the types of strategies that the laboratory used in each process of change according to content analysis, context and process them. The research is characterized as a case study of qualitative nature. The company stands out in your community through innovation, credibility and solid growth. For this research we used interviews and literature searches. The construction work was performed through a case study is a descriptive, historical and interpretive. Through a vision of schools of strategy, it became possible to relate the strategies adopted by the owners with the theory of the book Strategy Safari, as the school of learning, entrepreneurial, environmental, and cultural power.